MERGERS AND ACQUISITIONS IN DEVELOPING COUNTRIES: IS GENDER DIVERSITY DESIRABLE? - Satrio, Arif Budi (LPPM Universitas Jambi, 2026)
This study investigates the impact of gender diversity on target firms’ supervisory boards on merger and acquisition (M&A) decision-making in Indonesia, an emerging market characterized by concentrated ownership, weak shareholder protection, and the absence of gender quotas. While previous M&A studies have been viewed from the acquirer’s perspective, this study shifts the lens to the target firm’s governance structure, explicitly focusing on board gender composition. Drawing on resource dependence theory, agency theory, absorptive capacity theory, upper-echelons theory, and critical mass theory, this study aims to explain how board structure can affect a firm’s strategic outcomes. The investigation is conducted using robust regression on a comprehensive dataset of public companies in Indonesia that engaged in M&A activities between 2004 and 2022, spanning two crisis periods. The results show that larger supervisory boards are negatively associated with M&A activity, consistent with entrenchment concerns. Interestingly, although male-dominated boards tend to resist M&A attempts, females on the board, especially at the top, increase the likelihood of M&A. These findings contribute to the corporate governance literature by highlighting the strategic role of females on corporate boards in emerging markets, supporting the critical mass theory. The study shows that female leadership can influence high-level strategic decisions without regulatory mandates. These insights have practical implications for regulators and companies aiming to improve corporate governance effectiveness toward diversity rather than imposed quotas. Future studies could expand on these findings through cross-country comparisons and qualitative boardroom dynamics.